2019
DOI: 10.1371/journal.pone.0214509
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cadmium toxicity in wheat through plasma technology

Abstract: Cadmium (Cd) contamination in plant-derived food is a big concern. This study examines whether and how Ar/O 2 and Ar/Air plasma techniques lead to Cd detoxification in wheat. Treatment with Ar/O 2 and Ar/Air changed the seed surface and decreased the pH of seeds as well as the cultivation media. Generally, plants subjected to Cd treatment from seeds treated with Ar/O 2 and Ar/Air plasma showed considerable progress in morphology and total chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…In the first studies dedicated to the effect of NTP on plants, enhanced germination and growth parameters of treated plants were mostly observed. Effects of NTP were studied on many plant species–chicory [ 42 ], wheat [ 43 , 44 , 45 , 46 ], pepper [ 3 , 47 ], maize [ 36 ], pea [ 48 , 49 ], hemp [ 50 ], cucumber [ 3 ], oilseed rape [ 51 ], etc. Multiple works stated that there was no change in the final germination percentage, yet the germination speed was enhanced in NTP-treated seedlings [ 52 , 53 ].…”
Section: Interaction Of Non-thermal Plasma With Biological Materiamentioning
confidence: 99%
See 4 more Smart Citations
“…In the first studies dedicated to the effect of NTP on plants, enhanced germination and growth parameters of treated plants were mostly observed. Effects of NTP were studied on many plant species–chicory [ 42 ], wheat [ 43 , 44 , 45 , 46 ], pepper [ 3 , 47 ], maize [ 36 ], pea [ 48 , 49 ], hemp [ 50 ], cucumber [ 3 ], oilseed rape [ 51 ], etc. Multiple works stated that there was no change in the final germination percentage, yet the germination speed was enhanced in NTP-treated seedlings [ 52 , 53 ].…”
Section: Interaction Of Non-thermal Plasma With Biological Materiamentioning
confidence: 99%
“…Despite the minimal changes in CAT activity, the authors noticed that CAT isoenzyme expression showed significant changes in almost every group [ 68 ]. The importance of working gas for differences in the activity of antioxidant enzymes is illustrated in the study by Kabir et al [ 45 ]. They observed changes in antioxidant enzyme activity between NTP generated in Ar/O 2 and Ar/air mixtures.…”
Section: Interaction Of Non-thermal Plasma With Biological Materiamentioning
confidence: 99%
See 3 more Smart Citations